Serum Interleukin 6 Level and Nutrition Status as Potential Predictors of Clinical Leprosy Development Among Household Contacts in Endemic Areas. (2nd February 2022) - Oktaria, Salma; Anfasa, Fatih; Menaldi, Sri Linuwih; Bramono, Kusmarinah; Nijsten, Tamar E C; Thio, Hok Bing
Abstract: Background: Leprosy is a chronic infectious disease that can lead to severe lifelong disabilities. Close contacts of patients with leprosy have a higher risk of acquiring the disease. Nevertheless, there is a lack of reliable markers to predict Mycobacterium leprae infection. We aimed to identify new potential markers for developing clinical leprosy among contacts. Methods: Serum levels of interleukin (IL) 6, IL-8, IL-10, hemoglobin, ferritin, and transferrin saturation were measured in 67 patients with multibacillary leprosy (MB), 65 household contacts (HHCs) of MB patients, and 127 endemic controls (ECs). By means of multivariate logistic regression and receiver operating characteristic (ROC) analyses, we analyzed baseline variables and laboratory parameters that showed significant differences between MB in the HHC and EC groups and obtained the respective areas under the curve (AUC). Optimal cutoff values of the associated cytokines were also determined. Results: Elevated IL-6 level was observed in MB patients compared to HHCs and ECs ( P = .022 and .0041, respectively). Anemia and iron deficiency were also higher in the MB group compared to HHCs or ECs ( P < .001). Likewise, we observed an increased risk of having MB leprosy in underweight HHCs (odds ratio [OR], 2.599 [95% confidence interval CI, .991–6.820]) and underweight ECs (OR, 2.176 [95% CI, 1.010–4.692]). Further ROC analysis showed that high serum IL-6 level, underweight, anemia, and iron deficiency can discriminate leprosy from their HHCs (AUC, 0.843 [95% CI, .771–.914]; P = .000; optimal cutoff value of IL-6 = 9.14 pg/mL). Conclusions: Our results suggest that serum IL-6 and nutrition status could serve as potential prognostic markers for the development of clinical leprosy in infected individuals. Abstract : Low nutritional status and high interleukin 6 level >9.14 pg/mL may be used for the identification of infected individuals that will likely develop clinical leprosy. Further research is needed to explore the possibility of selecting contacts for prophylaxis using these parameters.